Internationally correlated jumps - Kuntara Pukthuanthong; Richard Roll (European Central Bank (ECB), 2012)
Stock returns are characterized by extreme observations, jumps that would not occur under the smooth variation of a Gaussian process. We find that jumps are prevalent in most countries. This has been little investigation of whether the jumps are internationally correlated. Their possible inter-correlation is important for investors because international diversification is less effective when jumps are frequent, unpredictable and strongly correlated. Public supervisors may also mind about widely correlated jumps, as they could bring down certain financial intermediaries. We investigate using daily returns on broad equity indexes from 82 countries and for several statistical measures of jumps. Various jump measures are not in complete agreement but a general pattern emerges. Jumps are internationally correlated but not as much as returns. Although the smooth variation in returns is driven strongly by systematic global factors, jumps are more idiosyncratic and most of them are found in Europe. Some pairs of correlated jumps occur simultaneously but not to the extent of correlated returns.
Keywords: G11; G15; 330; Correlation; diversification; jumps